Natural Gas Pricing in Countries of the Middle East and North Africa - Razavi, Hossein (2012)
This paper presents a quantitative framework for discussing the gas pricing policy in the countries of Middle East and North Africa (MENA) where gas prices are set directly or indirectly by the governments. It concludes that the price of gas in most MENA countries is substantially below its economic cost, resulting in wasteful use of gas and electricity, deployment of inefficient technologies, and huge burden on government budgets. The low gas price also causes a bias in favor of gas export projects while at the same time reduces investors interest in the upstream and downstream gas sector. The implications are most interesting about four countries Algeria, Qatar, Egypt, and Iran where each country has to revisit its gas allocation policy and where each government is trying to de-link investors interest from domestic gas prices.